Examining the effects of day reporting centers on recidivism: A meta-analysis. Issue 3 (3rd April 2019) - Wong, Jennifer S.; Bouchard, Jessica; Lee, Chelsey; Gushue, Kelsey
Abstract: Day reporting centers (DRCs) are a community-based correctional option that provide punishment and control while simultaneously assisting with rehabilitation and reintegration. The purpose of this study was to examine the effects of DRCs on the criminal recidivism of adult offenders. The current study meta-analyzed nine studies contributing 21 effect sizes (12 of which were independent). The findings show that, overall, DRCs do not differ from traditional supervision options in terms of recidivism outcomes. Additional analyses suggest that the magnitude of the treatment impact varies depending on the type of recidivism outcome measured, with studies limited to conviction showing a positive and significant reduction for DRCs. Further, front end DRCs were related to stronger treatment impact than back end DRCs. Inconsistent reporting of important variables concerning program characteristics and participant characteristics limited our ability to make recommendations for best practices.